The bright side and dark side of hybrid organic–inorganic perovskites - Walukiewicz, Wladek (2020)
The previously developed bistable amphoteric native defect (BAND) model is used for a comprehensive explanation of the unique photophysical properties and for understanding the remarkable performance of perovskites as photovoltaic materials. It is shown that the amphoteric defects in donor (acceptor) configuration capture a fraction of photoexcited electrons (holes) dividing them into two groups: higher energy bright and lower energy dark electrons (holes). The spatial separation of the dark electrons and the dark holes and the k-space separation of the bright and the dark charge carriers reduce electron hole recombination rates, emulating the properties of an ideal photovoltaic material with a balanced, spatially separated transport of electrons and holes. The BAND model also offers a straightforward explanation for the exceptional insensitivity of the photovoltaic performance of polycrystalline perovskite films to structural and optical inhomogeneities. The blue-shifted radiative recombination of bright electrons and holes results in a large anti-Stokes effect that provides a quantitative explanation for the spectral dependence of the laser cooling effect measured in perovskite platelets.